STUDI LITERATUR: DAMPAK PENGGUNAAN GADGET TERHADAP PRESTASI DAN KEBIASAAN BELAJAR SISWA SEKOLAH DASAR - Cindyana Wardhani, Marisa; Rania Muhsin; Shelvi Nerisa Arviana; Nabil Maulana Majid; Tasya Zaskia Putri; Delia Indrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has made gadget use an integral part of elementary school students' daily lives. While gadgets offer potential benefits as interactive learning media, excessive and uncontrolled use may negatively affect students’ academic performance and study habits. This study aims to analyze the impact of gadget use on students’ learning achievement and study habits through a literature review approach. The research employs a qualitative method with a library research design by examining relevant scientific articles, journals, and supporting literature. Data were collected through documentation techniques and analyzed using content analysis to identify patterns, relationships, and key findings. The results indicate that gadget use has a dual impact. On the one hand, it can enhance students’ motivation, access to learning resources, and engagement when used appropriately. On the other hand, excessive use especially for non-educational purposes such as gaming and social media tends to reduce concentration, learning discipline, and academic performance. Furthermore, the lack of parental and teacher supervision strengthens the negative effects of gadget use. Therefore, proper guidance and controlled usage are essential to maximize the educational benefits of gadgets while minimizing their adverse impacts on elementary school students.